Echography of Self: Autobiographical Documentary and the Paths to Subjectivity (Self)Representation - Lagos Labbé, Paola (Universidad de Chile. Instituto de la Comunicación e Imagen, 2011)
The article reviews the main theoretical discussions on autobiographical documentary, regarding its most recurrent narrative, formal and aesthetic strategies, in order to represent subjectivity. The introspective feature that characterizes "autobiografilmes" is delimited in a private, intimate, quotidian, affective, emotional, confessional realm, adopting settings that gather different autorepresentational resources to shape a distinct space, time and voice that come together to evoke the "self". Tracing crucial expressions of this type of non fiction film, such as diaries and self-portraits, the article closes with a projection on the challenges of contemporary autobiographical filmmaking under vertiginous technological changes linked to digital video and the proliferation of virtual platforms.